2012
DOI: 10.1186/1617-9625-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking among doctors in mainland China: a study from Shandong province and review of the literature

Abstract: BackgroundTobacco control represents a key area in which doctors can make a significant positive impact on their patients’ lives. Despite this fact, however, doctors in certain regions of China are known to smoke tobacco at rates similar to or even exceeding those seen within the general population.ObjectiveThis study sought to investigate the smoking habits of doctors at a teaching hospital in Shandong province, as well as providing a brief review of smoking research that has been conducted among doctors else… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…105 The prevalence of smoking among physicians remains substantial (>50% of male physicians in many cities/provinces). 106,107 Thus, awareness of the health hazards of smoking remains poor and tobacco control policies face many barriers and challenges in China. 108,109 …”
Section: Resultsmentioning
confidence: 99%
“…105 The prevalence of smoking among physicians remains substantial (>50% of male physicians in many cities/provinces). 106,107 Thus, awareness of the health hazards of smoking remains poor and tobacco control policies face many barriers and challenges in China. 108,109 …”
Section: Resultsmentioning
confidence: 99%
“…Here, most participants reported smoking-related health problems and medical advice as the main reasons for quitting, and the latter was found to be the most commonly cited smoking-cessation trigger in China 31 . Few studies have reported the importance of physician advice for quitting in China and this may reflect the high smoking prevalence, 21%-61%, amongst Chinese physicians 32 . On migration to Glasgow, most participants here had tried to quit with various triggers cited.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the important role of physicians in tobacco control, a large proportion of male physicians in China are smokers; but smoking prevalence among female physicians is very low, reflecting low prevalence among women at large in China 4. Previous studies have shown that smoking rates among male physicians range between 26% and 61% 2 4 6 14 15…”
Section: Introductionmentioning
confidence: 99%